Leucocytes isolated from simply frozen whole blood can be used in human biomonitoring for DNA damage measurement with the comet assay. (26th November 2013) - Akor‐Dewu, Maryam B.; El Yamani, Naouale; Bilyk, Olena; Holtung, Linda; Tjelle, Torunn E.; Blomhoff, Rune; Collins, Andrew R.
<x xml:space="preserve">Abstract</x> Preservation of human blood cells for DNA damage analysis with the comet assay conventionally involves the isolation of mononuclear cells by centrifugation, suspension in freezing medium and slow freezing to −80 °C—a laborious process. A recent publication (Al‐Salmani et al. Free Rad Biol Med 2011; 51: 719–725) describes a simple method in which small volumes of whole blood are frozen to −20 or −80 °C; on subsequent thawing, the comet assay is performed, with no indication of elevated DNA strand breakage resulting from the rapid freezing. However, leucocytes in whole blood (whether fresh or frozen) are abnormally resistant to damage by H2O2, and so a common test of antioxidant status (resistance to strand breakage by H2O2) cannot be used. We have refined this method by separating the leucocytes from the thawed blood; we find that, after three washes, the cells respond normally to H2O2. In addition, we have measured specific endogenous base damage (oxidized purines) in the isolated leucocytes, using the enzyme formamidopyrimidine DNA glycosylase. In a study of blood samples from 10 subjects, H2O2 sensitivity and endogenous damage—both reflecting the antioxidant status of the cells—correlated significantly. This modified approach to sample collection and storage is particularly applicable when the available volume of blood is limited and has great potential in biomonitoring and ecogenotoxicology studies where samples are obtained in the field or at sites remote from the testing laboratory. Copyright © 2013 John Wiley & Sons, Ltd.